Экранирование магнитного поля промышленной частоты стенами жилых домов - Пелевин, Дмитрий Евгеньевич (НТУ "ХПИ", 2015)
Проведены экспериментальные исследования эффективности экранирования магнитного поля частотой 50 Гц строительными материалами, железобетонными стенами и панельными жилыми домами. Установлено, что магнитное поле частотой 50 Гц практически без ослабления проникает через стены домов, в том числе и железобетонные.

To investigate the effectiveness of the screening of the magnetic field at 50 Hz by the walls of house. Methodology. To study the effectiveness of the screening we used the measurements of the magnetic field 1) in the area of the shielding screen 2) in the same area without the shielding screen 3) the calculation of the shielding effectiveness by measuring. Results. We have carried out experimental investigations of the effectiveness of screening of the magnetic field at 50 Hz by the building materials, concrete walls and paneled houses. Originality. First it is experimentally established that the magnetic field with frequency of 50 Hz penetrates through walls of buildings including reinforced concrete buildings practically without any decrease. Practical value. The results obtained should be considered when assessing the hygienic level of the magnetic field in a residential area, located near air and cable lines.
Screening magnetic fields of the power frequency by the walls of houses
Keywords: промышленная частота; магнитное поле; экранирование; жилые помещения; жилищный фонд; power frequency; magnetic field; screening; walls of houses; experimental investigations